Institutional Asset Management. - Sossong, Andreas (Diplomica Verlag, 2014)
This study examines the current legislature and best practice corporate governance for institutional investors in Germany and the United States. Differences in investment regulation, compliance and disclosure requirements, as well as expense and tax schemes are identified for insurance companies and the pension fund industry. Based on current academic literature, hypotheses about the impact of different regulatory regimes are derived and tested empirically in a comparison between Germany and the United States over the last five years. Differences in asset allocation between the two countries a.